PENINGKATAN PENGETAHUAN TENTANG PENCEGAHAN PENYALAHGUNAAN NAPZA MELALUI MEDIA EDUKATIF PADA MAHASISWA PENJAS SEMESTER 2 UNIVERSITAS AISYAH PRINGSEWU - Desti Kurnia Putri; Dellia Dwi Kurnia; Elisya Elisya; Nabila Marthatilova; Septia Cahyani; Dwi Ilpa Ningsih; Mohammad Lazim; Rohana Maya Sari (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Law of the Republic of Indonesia Number 35 of 2009 and Law of the Republic of Indonesia Number 5 of 1997 state that narcotics and psychotropic substances are substances that can affect the central nervous system and cause dependence. The National Narcotics Agency (BNN, 2021) noted that the 15–35 age group is the largest user of narcotics in Indonesia, with a prevalence of 1.95% of the total population. Drug use among male adolescents is 4.9%, with the highest use being through smoking or inhaling (2.5%), and it can increase premarital sexual behavior (Hasanah, 2022). In Lampung Province in 2023, there were 1,516 cases of drug abuse, with the highest number of cases among high school students (699, or 47.1%) (Ulinnuha, 2024). Preventing drug abuse requires a comprehensive strategy through multi-stakeholder collaboration, as drug abuse has detrimental effects on both physical and psychological health (Azhar, 2023).